2005
DOI: 10.1681/asn.2005010063
|View full text |Cite
|
Sign up to set email alerts
|

Essential Hypertension, Progressive Renal Disease, and Uric Acid

Abstract: Hypertension and hypertension-associated ESRD are epidemic in society. The mechanisms responsible for renal progression in mild to moderate hypertension and those groups most at risk need to be identified. Historic, epidemiologic, clinical, and experimental studies on the pathogenesis of hypertension and hypertension-associated renal disease are reviewed and an overview/hypothesis for the mechanisms involved in renal progression is presented. There is increasing evidence that hypertension may exist in one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
175
1
9

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(192 citation statements)
references
References 148 publications
7
175
1
9
Order By: Relevance
“…Especially diuretics are associated with an increase in serum UA levels, and it is suggested that raising UA levels can stimulate the renin-angiotensin-system accelerating the development of renal microvascular disease and thereby predispose the patient to renal disease progression. 12 Thereupon, in humans, asymptomatic hyperuricemia induced progression of CKD and worsened control of hypertension, an effect that was blocked by angiotensin-converting enzyme inhibitor treatment when allopurinol therapy was withdrawn, 34 which could not be examined in this study. Moreover, accurate UA-lowering therapy is safe and does not deteriorate kidney function 32 ; therefore, it seems unlikely that accurate UA-lowering therapy can substantially confound the relationship between UA and development of new-onset kidney disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Especially diuretics are associated with an increase in serum UA levels, and it is suggested that raising UA levels can stimulate the renin-angiotensin-system accelerating the development of renal microvascular disease and thereby predispose the patient to renal disease progression. 12 Thereupon, in humans, asymptomatic hyperuricemia induced progression of CKD and worsened control of hypertension, an effect that was blocked by angiotensin-converting enzyme inhibitor treatment when allopurinol therapy was withdrawn, 34 which could not be examined in this study. Moreover, accurate UA-lowering therapy is safe and does not deteriorate kidney function 32 ; therefore, it seems unlikely that accurate UA-lowering therapy can substantially confound the relationship between UA and development of new-onset kidney disease.…”
Section: Discussionmentioning
confidence: 97%
“…10 Recent epidemiologic and experimental evidence suggests a role for UA not only as a marker of reduced kidney function and an independent cardiovascular risk factor 11 but also as a causal risk factor for the development and progression of renal disease. 5,9,12 Two large epidemiologic studies demonstrated that UA was a major predictor for the development of incident renal disease, 13,14 but none of these studies evaluated the amount of its real role as an independent risk factor. Furthermore, hyperuricemia is associated with a greater incidence of ESRD.…”
mentioning
confidence: 99%
“…Uric acid has been related to cardiovascular morbidity and mortality in a number of previous studies. 20,21 In the MONICA cohort, hyperuricemia was associated significantly with cardiovascular mortality, independent of body mass index, hypertension, diuretic or alcohol use and smoking. 22 Uric acid has also been identified as an independent predictor of microalbuminuria in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 These studies imply a hypothesis that uric acid might have synergistic effects with other risk factors during atherogenesis. We particularly assessed the interactions between SUA and other metabolic risk factors in relation to hypertension.…”
Section: Introductionmentioning
confidence: 92%